Teachers and the birth rate : the demographic dynamics of a service population - Denton, Frank T. [Verfasser]; Feaver, Christine H. [Verfasser]; Spencer, Byron G. [Verfasser] (My University, 1994)
"A theoretical model is developed in which the market for teachers is linked to the time path of fertility in the general population. The model is simple in its components but when the components are combined they form a complex long-memory dynamic system. Simulation experiments are carried out to investigate the effects of changes in fertility rates on supply/requirements imbalances in the teachers' market, the median age of teachers, and other variables. The model (and by implication, the real-world system) is found to be highly volatile in response to fertility variations." (author's abstract, IAB-Doku) ((en)) In dem Beitrag wird ein theoretisches Modell entwickelt, dass den Arbeitsmarkt für Lehrer in Abhängigkeit von der Geburtenrate der Bevölkerung untersucht. (IAB)
Lehrer und die Geburtenrate
Keywords: P 3.2.3 Lehrer; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; G 2.4.3 Privater & Familiärer Wandel; Lehrer; Arbeitskräftebedarf; Geburtenhäufigkeit; Auswirkung; Quantitative Angaben